2017
DOI: 10.1042/cs20171121
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-200c is up-regulated in paediatric patients with familial hypercholesterolaemia and correlates with miR-33a/b levels: implication of a ZEB1-dependent mechanism

Abstract: Hypercholesterolaemia provokes reactive oxygen species (ROS) increase and is a major risk factor for cardiovascular disease (CVD) development. We previously showed that circulating expression levels were up-regulated in children with familial hypercholesterolaemia (FH). control cholesterol homoeostasis and recently has been demonstrated to directly target the transcription factor zinc finger E-box-binding homeobox 1 (ZEB1). The latter acts in a negative feedback loop with the family. Our previous studies showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…The miR-200 family, comprising of miR-200b, miR-200c and miR-429, is a well-known miRNA cluster which is highly investigated in anti-cancer studies [15]. Also, it has been previously shown that miR-200c is upregulated in CVDs [16]. Here, we elucidated the role of miR-200c in SARS-CoV-2 infection where the overexpression of miR-200c represses ACE2 expression in both rat and human cardiomyocytes.…”
Section: Discussionmentioning
confidence: 84%
“…The miR-200 family, comprising of miR-200b, miR-200c and miR-429, is a well-known miRNA cluster which is highly investigated in anti-cancer studies [15]. Also, it has been previously shown that miR-200c is upregulated in CVDs [16]. Here, we elucidated the role of miR-200c in SARS-CoV-2 infection where the overexpression of miR-200c represses ACE2 expression in both rat and human cardiomyocytes.…”
Section: Discussionmentioning
confidence: 84%
“…The miR-200 family was shown to be induced by oxidative stress and to play an important role in endothelial function; in particular, miR-200c induces EC apoptosis, senescence, and dysfunction [24,25]. Moreover, circulating miR-200c is upregulated in FH in pediatric age, a disease characterized by oxidative stress increase and precocious atherosclerosis [26]. miR-200c increases also in carotid plaques, and its expression is higher in unstable vs. stable plaques and is upregulated in the plasma of atherosclerotic patients.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Thus, miR-200c upregulation causes ROS increase and NO production decrease [25]. Moreover, we have previously shown that circulating miR-200c is significantly upregulated in familial hypercholesterolemia (FH) patients in pediatric age [26], a disease associated with high oxidative stress levels and early atherosclerosis [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-200c also plays a major role in cardiovascular diseases (19). miRNA-200c is upregulated in plaques and plasma of atherosclerotic patients, being further enhanced in unstable vs stable carotid plaques (23) and in plasma of children with familiar hypercholesterolemia (24).…”
Section: The Mirna-200 Familymentioning
confidence: 99%
“…miRNA-200c also plays a major role in cardiovascular diseases ( 19 ). miRNA-200c is upregulated in plaques and plasma of atherosclerotic patients, being further enhanced in unstable vs stable carotid plaques ( 23 ) and in plasma of children with familiar hypercholesterolemia ( 24 ). miRNA-200c was found upregulated in cardiomyopathies induced by doxorubicin (DOX) in mice as well as in human cardiac mesenchymal progenitor cells exposed to DOX ( 25 ).…”
Section: Mirnas Involved In Aging and Regenerationmentioning
confidence: 99%